The Effectiveness of Group Counseling in Modifying Attitudes toward Drugs among Inmates - Tumanggor, Athalia A. Aptanta; Nirwana, Herman (Bisma The Journal of Counseling, 2024)
The increase in drug abuse cases in Indonesia, especially among women, raises concerns about its impact on physical health and social behavior. One important determinant of drug abuse behavior is an individual's attitude towards the substance. Permissive or positive attitudes towards drugs are known to increase the tendency to use. This study specifically aims to examine the effectiveness of group guidance services in modifying prisoners' attitudes towards drugs. This study used a quantitative approach with a quasi-experimental method and time series design. The research subjects involved nine inmates and one former inmate of drug cases who participated in a series of group guidance sessions. Data were obtained through the instrument of Attitude toward Drugs Checklist which was prepared based on Likert scale. Data analysis techniques used include the N-gain test to assess the increase in attitude change and the Wilcoxon test to test the significance of differences before and after the intervention. The results showed that group guidance services were significantly able to change prisoners' attitudes towards drugs, with a Z value of -2.810 and Asymp. Sig. (2-tailed) of 0.005. These findings indicate that the alternative hypothesis (Ha) is accepted. Thus, it can be concluded that group guidance services are an effective approach in reducing permissive attitudes towards drugs, and have the potential to be a supporting strategy in rehabilitation and drug abuse prevention programs in correctional institutions.